Prevalence of hypodontia and supernumerary teeth in a German cleft lip with/without palate population - Liesa Heidi Möller; Winnie Pradel; Tomasz Gedrange; Ute Ulrike Botzenhart (BMC, 2021)
Abstract Background The distribution of dental abnormalities among cleft patients concerning cleft type frequently poses ambiguity wherefore the aim of this study was to evaluate the prevalence of hypodontia and supernumerary teeth in an exemplary German cleft population dependent on the cleft type. Methods Radiographs and dental records of cleft patients, which had been treated and followed up in the Department of Oral and Maxillofacial Surgery, University Hospital Carl Gustav Carus Campus, Dresden, Germany (investigation period of 22 years) were evaluated concerning hypodontia and supernumerary teeth dependent on the cleft type. Out of 386 records, 108 patients met the inclusion criteria: non-syndromic cleft of the alveolus with or without palate (CL/P), at least one clear panoramic x-ray, sufficient dental records. Statistical analysis was performed using x-square and binominal test (p ≤ 0.05). Results Hypodontia was more frequent (54/50%) than supernumerary teeth (36/33.3%) and was more common in bilateral clefts of the lip and palate (BCLP) (70.1%) than in unilateral clefts of the lip and palate (UCLP) (51.6%) or clefts of the lip and alveolus (CLA) (34.5%) (p << 0.001). There was an average of 0.9 missing teeth per patient, thereof the upper lateral incisor was most often affected (23.2%). In contrast, supernumerary teeth were more frequent in CLA (51.7%; p = 0.014) than UCLP (29.0%) and BCLP patients (17.6%). Conclusion The prevalence for numerical dental anomalies was significantly different among the cleft types. Hypodontia significantly increased with the extend of the cleft, whereas the prevalence of supernumerary teeth decreased.